The Diversification of the Economy of the Ulytau Region through the Development of Tourism - A. T. Tleuberdinova; D. M. Salauatova (Экономика: стратегия и практика)
The purpose of the study is to determine the possibilities for diversifying the economy of the Ulytau region through the development of the tourism industry. Some regions of Kazakhstan are characterized by monoprofile regions, the problems of which are exacerbated during the crisis. A monoprofile characterizes the spatial organization of the economy of the Ulytau region as a consequence of the predominant orientation towards the development of non-ferrous metallurgy. As evidenced by the events of the world arena in recent years, excessive dependence on commodity markets in the long term, one way or another, creates a threat of inhibition and a deformation impact on the trajectory of the socio-economic development of the region. This condition determined the topic of this article and its theoretical and practical significance. The study uses a systematic approach. The methodological basis of the study is based on general scientific methods: analysis and synthesis of statistical data, logical method, method of comparative analysis, and methods for assessing the level of diversification of the regional economy. As a result of the study, a diagnosis of the state of diversification of the economy of the Ulytau region was carried out, and the tourism sector was defined as a direction for achieving the sustainability of the region’s economy due to the presence of rich tourism potential. Conclusions and suggestions based on the results of the study can be used in the development of regional programs and concepts for the development of the Ulytau region.